Development of a Comprehensive Mobility Discharge Assessment Framework for Older Adults Transitioning from Hospital-To-Home Through Evidence Synthesis and e-Delphi Process - Kalu, Michael (My University, 2022)
Functional status independently predicts older adults’ hospital readmission. Despite this, clinicians often do not complete mobility assessments during the hospital-to-home transition for older adults, mainly because factors within the seven mobility determinants have not been comprehensively represented in mobility measures. Phase 1 of this PhD thesis (manuscripts 1, 2 and 3) comprised a series of scoping reviews that comprehensively described factors within each of the seven mobility determinants [cognitive, financial, environmental, personal, physical, psychological and social] and their association with self-report and performance-based mobility outcomes. A total of 772 largely cross-sectional articles published in 51 countries were reviewed which identified 84 factors: cognitive (n=8), psychological (n=18), social (n=9); personal (n=11), environmental (n=17), financial (n=3), and physical (n=18), and their association with mobility outcomes. Phase 2 of this PhD thesis (manuscripts 4, 5 and 6) was an e-Delphi study aimed at prioritizing and achieving consensus on mobility factors across the seven determinants considered critical to include in the Comprehensive Mobility Discharge Assessment Framework (CMDAF) for older adults transitioning from hospital-to-home. Sixty international experts (seven older adults, nine family caregivers, 24 clinicians and 20 researchers) from nine countries prioritized 43 out of 91 factors across all the seven determinants to be included in the CMDAF, except for financial determinants. Experts provided reasons for their ratings. They conditionally placed importance on certain factors over other factors based on the uniqueness of each older adult; healthcare roles and practice-based approaches; and service availability and regional [context] meaning of some of the factors. The positive and negative role of factors influencing mobility was another reason experts rated the way they did. This is the first step in developing CMDAF. Future research should examine how and which measurement instruments best measure these 43 mobility factors to advance the CMDAF. Further examining the feasibility and practicality of using CMDAF in hospital-to-home clinical transition settings is recommended.
Keywords: Mobility; Older adults; Hospital-to-home transition; Aging; Discharge; e-delphi process; Scoping reviews; Qualitative content analysis